2022
DOI: 10.1039/d1ra04974g
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial peptide GL13K immobilized onto SLA-treated titanium by silanization: antibacterial effect against methicillin-resistant Staphylococcus aureus (MRSA)

Abstract: Herein, an antimicrobial peptide coating was fabricated on SLA-treated titanium surface. The coating has shown significant antibacterial effect against MRSA with no cytotoxicity against osteoblast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…[ 59 ] Moreover, the AMP GL13K immobilized onto titanium exhibited strong contact‐ and release‐killing abilities. [ 60 ] Since the developed PCLdiUPy coating with 5 mol% UPy‐SAAP‐148 also showed some release of the UPy‐SAAP‐148GG, this antimicrobial coating may provide this desired combined strategy in the fight against BAI. This supramolecular approach makes it possible to coat complex‐shaped implants and using the UPy moiety allows incorporation of a selection of antimicrobial agents and cell instructive molecules, thereby making it a very versatile technique that can be personalized to the patient's needs.…”
Section: Resultsmentioning
confidence: 99%
“…[ 59 ] Moreover, the AMP GL13K immobilized onto titanium exhibited strong contact‐ and release‐killing abilities. [ 60 ] Since the developed PCLdiUPy coating with 5 mol% UPy‐SAAP‐148 also showed some release of the UPy‐SAAP‐148GG, this antimicrobial coating may provide this desired combined strategy in the fight against BAI. This supramolecular approach makes it possible to coat complex‐shaped implants and using the UPy moiety allows incorporation of a selection of antimicrobial agents and cell instructive molecules, thereby making it a very versatile technique that can be personalized to the patient's needs.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial and anti-inammatory role of the antimicrobial peptide GL13K has been studied in recent years. 15,22 In this study, AMP GL13K was continuously released from the titanium surface for two weeks by a thermosensitive hydrogel, resulting in early antibacterial and anti-inammatory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al reported that AMP GL13K exhibited antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA). 22 Further, the release of GL13K prevented the formation of a microbial biofilm, which was a major factor leading to the failure of osseointegration. Microbial biofilms are highly structured matrix-enclosing sessile bacterial communities, which hinder bacterial eradication.…”
Section: Discussionmentioning
confidence: 99%